The Role of Real Estate Loans in Alleviating the Housing Crisis in Iraq for the Period (2016-2024): A Field Study - Dawai, Jassim Mushtat; Hanzal , Hanan Jumaa (The Journal of Accounting and Management, 2025)
Real estate loans are a defensive mechanism to mitigate economic crises in general, and the housing sector in particular. This requires the involvement of banks and financial institutions specializing in housing loans, as they finance transactions that enable middle-income groups to own homes. Individuals may seek to acquire a ready-made home, build a home, or buy and sell a home based on the designs. In exchange, the financier receives interest, which the borrower is obligated to pay, along with repaying the loan amount. This occurs in gradual stages, while employing a set of financial and administrative techniques, each of which has its own significance in a sound and valid contract. The research presented a theoretical perspective on the most important points raised by the researchers regarding the research variables, in addition to the analytical aspect included in estimating the housing deficit in Iraq. The research attempted to answer the question that embodied the problem: “How can real estate loans contribute to solving the housing crisis in Iraq?” The research reached a set of conclusions, the most important of which are: “There are routine administrative, financial, and legal procedures that delay the process of granting real estate loans, and there are no effective strategic plans at the national and provincial levels to solve the housing problem.” The research also reached a set of recommendations, including: “Establishing a central administration to manage housing activity that takes into account all necessary aspects and involves the private sector, and providing a comprehensive national strategy to address the housing problem in which all relevant parties participate.”